Essential C an introduction for scientists and engineers - Andersen, Paul K. (Saunders College pub., 1995)
Essential C is intended for students who have had no prior programming experience. Providing a simple and brief introduction to programming in C makes this text suitable for a first semester, freshman level course. Only the basics a students needs to understand and write useful C programs are presented and explanations using computer jargon are avoided. Examples are referred to whenever possible. The topics have been carefully chosen for their relevance to practical scientific and engineering programming. Although the text is written with the scientific and engineering students in mind, it should be suitable in other disciplines as well.